2014
DOI: 10.1097/fjc.0000000000000079
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Analysis of Curcumin-induced Polarization of Murine RAW264.7 Macrophages

Abstract: This study aimed to investigate the effects of curcumin on macrophages polarization and possible mechanism involved, and to analyze the molecular basis of its antiatherosclerosis activity. RAW264.7 macrophages (M0) and M1 macrophages were treated with curcumin at 0, 6.25, 12.5, and 25 μmol/L with or without GW9662. Using real-time polymerase chain reaction and Western blot analysis, we examined the phenotype markers of M1 [iNOS, interleukin (IL)-1β, IL-6, and MCP-1] and M2 (KLF4, FIZZ1, and MGL1] macrophages. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(26 citation statements)
references
References 47 publications
0
26
0
Order By: Relevance
“…Yin et al showed that curcumin inhibited caspase-1 activation and IL-1β secretion through suppressing lipopolysaccharide (LPS) priming and NLRP3 inflammasome in mouse bone marrow-derived macrophages, and confirmed these results in vivo in a model of high-fat diet-induced insulin resistance in wild-type C57BL/6 mice [72]. Interestingly, in an in vitro study, Chen et al demonstrated that curcumin inhibits the M1 inflammatory phenotype of RAW264.7 macrophages as a result of the direct activation of the inhibitor protein κB-α (IkB-α) and polarizes the macrophages to become anti-inflammatory M2 phenotype through the activation of PPARγ [73]. Later on, the same group reported that curcumin dramatically reduced oxLDL-induced IL-1β, IL-6 and TNF-α cytokine production in M1 derived from M0 RAW264.7 macrophages [74].…”
Section: Introductionmentioning
confidence: 70%
“…Yin et al showed that curcumin inhibited caspase-1 activation and IL-1β secretion through suppressing lipopolysaccharide (LPS) priming and NLRP3 inflammasome in mouse bone marrow-derived macrophages, and confirmed these results in vivo in a model of high-fat diet-induced insulin resistance in wild-type C57BL/6 mice [72]. Interestingly, in an in vitro study, Chen et al demonstrated that curcumin inhibits the M1 inflammatory phenotype of RAW264.7 macrophages as a result of the direct activation of the inhibitor protein κB-α (IkB-α) and polarizes the macrophages to become anti-inflammatory M2 phenotype through the activation of PPARγ [73]. Later on, the same group reported that curcumin dramatically reduced oxLDL-induced IL-1β, IL-6 and TNF-α cytokine production in M1 derived from M0 RAW264.7 macrophages [74].…”
Section: Introductionmentioning
confidence: 70%
“…However, other studies have indicated that oral administration of a curcumin solution (3000 mg/kg) significantly reduces tumor neocapillary density and serum VEGF levels in mice with HepG2 hepatocellular carcinoma [62]. Furthermore, although treatment of RAW264.7 macrophages with 1 mM of hydrazinocurcumin encapsulated nanoparticles induced polarization of macrophages from M2 to M1 phenotype through inhibition of STAT3 [63], 25 μmol/L of curcumin, on the contrary, stimulated polarization of these cells into M2 phenotype via activation of proliferator-activated receptor gamma and secretion of IL-4 or IL-13 [64. 65].…”
Section: Natural Anti-angiogenic Compounds Derived From Plantsmentioning
confidence: 99%
“…Previous findings indicated that curcumin be able to not only directly stimulate the polarization of macrophages to M2 phenotype, but also induce switching of macrophages from M1 to M2 phenotype [7][8][9]. Curcumin, as a major bioactive constituent in turmeric (Curcuma longa), has been described as a brilliant molecule among lots of naturally occurring substances for powerful anti-inflammatory, antioxidant, antidiabetic and anticancer activities [10][11][12][13][14][15].…”
Section: Introductionmentioning
confidence: 99%